Comparative Analysis of Increasing Online Purchase Decisions during the Covid-19 Pandemic Period among Tangerang area and South Tangerang - Diana Silaswara; Andy Andy; Tjong Se Fung (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The basis of research aims to determine the impact of the Covid-19 pandemic, especially on the factors that trigger online purchase decisions made. This study is a comparative study because it compares the effect of Online Promotion (X1) and Lifestyle (X2) Online Purchasing Decisions (Y) between the areas of Tangerang City and South Tangerang. The research questionnaire was distributed within 11 days and obtained 165 valid respondents. The questionnaire was processed using the SPSS 20 program, and from the validity test results it turns out that only 38 statements are valid. From other test results, it was found that the statement was constant, normally distributed and did not occure heteroscedastidity and multicollinearity in the two regression equations formed in each region. The relationship between variables in each region is not very strong. The results obtained are that all hypotheses are proven, namely: Online Promotion and Lifestyle Influence on Purchasing Decisions, as well as proven that there are differences in influencing factors in the two regions. The difference that occurs is in Tangerang City the dominant purchasing decision is influenced by the Online Promotion offered, while in South Tangerang the two factors affect equally.